Development of a Solar-reflective Ceramic Tile Ready for Industrialization. (2016) - Ferrari, Chiara; Muscio, Alberto; Siligardi, Cristina
Abstract: Solar-reflective surfaces represent an effective countermeasure to UHI. The market of "cool" materials is dominated by polymeric solutions which, under UV exposure, are damaged. On the other hand, an increasing attention was paid recently to ceramic-based solar-reflective surfaces, characterized by very long lifespan. A ceramic tile is typically made by a three layers structure: substrate-engobe-glaze. This structure has been exploited to develop a cool ceramic tile that can be produced in the same production facilities of common products to create a whole tile by merging technological results and industrial production needs, to achieve a compromise between performance and costs.